2016
DOI: 10.3389/fmicb.2016.01900
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation Using Visible Light Plus Water-Filtered Infrared-A (vis+wIRA) and Chlorine e6 (Ce6) Eradicates Planktonic Periodontal Pathogens and Subgingival Biofilms

Abstract: Alternative treatment methods for pathogens and microbial biofilms are required due to the widespread rise in antibiotic resistance. Antimicrobial photodynamic therapy (aPDT) has recently gained attention as a novel method to eradicate pathogens. The aim of this study was to evaluate the antimicrobial effects of a novel aPDT method using visible light (vis) and water infiltrated infrared A (wIRA) in combination with chlorine e6 (Ce6) against different periodontal pathogens in planktonic form and within in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 48 publications
1
26
1
2
Order By: Relevance
“…Our data revealed that 75 mg/L and 100 mg/L PDZ-mediated aPDT promoted 0.97 and 1.12 log 10 reductions in CFU/mL, respectively. In contrast to our outcomes, a previous study demonstrated a significant effect against F. nucleatum ATCC 25586, with more than a 3 log 10 reduction when aPDT with visible light (vis) and water infiltrated infrared A (wIRA) were combined with Ce6[50]. The strong antimicrobial effect of aPDT against F. nucleatum…”
contrasting
confidence: 99%
See 4 more Smart Citations
“…Our data revealed that 75 mg/L and 100 mg/L PDZ-mediated aPDT promoted 0.97 and 1.12 log 10 reductions in CFU/mL, respectively. In contrast to our outcomes, a previous study demonstrated a significant effect against F. nucleatum ATCC 25586, with more than a 3 log 10 reduction when aPDT with visible light (vis) and water infiltrated infrared A (wIRA) were combined with Ce6[50]. The strong antimicrobial effect of aPDT against F. nucleatum…”
contrasting
confidence: 99%
“…Despite the efficacy of aPDT against biofilm viability, an antimicrobial effect was not observed to ensure antibacterial properties since we obtained less than a 3 log 10 CFU reduction [57]. In contrast, an antimicrobial effect of aPDT using vis+wIRA combined with Ce6 was recently reported against different periodontal pathogens in a pool of subgingival oral biofilms with disruption of their tridimensional structures before the application of aPDT [50]. This disruption in the architecture of a biofilm can potentiate the effects of antimicrobial strategies.…”
Section: Accepted Manuscriptmentioning
confidence: 74%
See 3 more Smart Citations